Design optimisation of non-axisymmetric exhausts for installed civil aero-engines - Hueso Rebassa, Josep; MacManus, David G.; Tejero, Fernando; Goulos, Ioannis; Sánchez-Moreno, Francisco; Sheaf, Christopher T. (Elsevier, 2023)
Future civil aero-engines are likely to operate with higher bypass-ratios (BPR) than current power-plants to improve propulsive efficiency and reduce specific thrust. This will probably be accompanied by an increase of fan diameter and size of the power plant. Consequently, future configurations are likely to require more close-coupled installations with the airframe due to structural and ground clearance requirements. This tendency may lead to an increase in the adverse installation effects which could be mitigated with non-axisymmetric exhausts. However, due to the prohibitive computational cost, limited regions of the design space have been studied. For this reason, a relatively low-cost design approach for the integrated system is required. The aim of this work is to establish a method to map the non-axisymmetric exhaust design space where the effects of the propulsion system installation are taken into account. The methodology relies on the generation of a design database using inviscid computational fluid dynamics (CFD) methods. This is used to characterise the design space, identify the dominant design parameters and build response surface models for optimisation. The candidate designs that arise from the optimisation are assessed with viscous CFD simulations to assess the aerodynamic mechanisms and performance characteristics. The result is a set of design recommendations for installed configurations with non-axisymmetric exhausts. The method is an enabler for the optimisation of installed propulsion systems and has provided an exhaust design with a 0.7% improvement on net vehicle force relative to an axisymmetric exhaust, for a close coupled configuration where the fan cowl is overlapped with the wing. A reduction in net vehicle force is expected to lead to a similar reduction in cruise fuel burn.